2019
DOI: 10.1038/s41408-019-0237-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the risk of second primary malignancies among survivors of chronic lymphocytic leukemia

Abstract: With improving survivorship in chronic lymphocytic leukemia (CLL), the risk of second primary malignancies (SPMs) has not been systematically addressed. Differences in risk for SPMs among CLL survivors from the Surveillance, Epidemiology, and End Results (SEER) database (1973–2015) were compared to risk of individual malignancies expected in the general population. In ~270,000 person-year follow-up, 6487 new SPMs were diagnosed with a standardized incidence ratio (SIR) of 1.2 (95% CI:1.17–1.23). The higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 32 publications
9
58
1
Order By: Relevance
“…Other studies have found AML/MDS in 3–5% of fludarabine treated patients which is in line with our findings 16,18 . Higher risk of treatment associated AML/MDS was also seen in another study of fludarabine‐based combination therapy (fludarabine and cyclophosphamide (FC), RFC and RFC with mitoxantrone) in treated versus untreated patients 19 .…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have found AML/MDS in 3–5% of fludarabine treated patients which is in line with our findings 16,18 . Higher risk of treatment associated AML/MDS was also seen in another study of fludarabine‐based combination therapy (fludarabine and cyclophosphamide (FC), RFC and RFC with mitoxantrone) in treated versus untreated patients 19 .…”
Section: Discussionsupporting
confidence: 91%
“…Prevalence of t‐MDS and t‐AML in chemotherapy/chemoimmunotherapy‐treated patients with CLL is about 1%‐8% in CLL populations reported from tertiary referral institutions or clinical trials with median age between 60 and 65 years, for example, about 10 years younger than the “real‐world” CLL population . Reports on a general unselected CLL population are based on cancer registries . Among 15 915 patients with CLL surviving at least 1 year after diagnosis of CLL registered in 11 SEER registries in USA between 1992 and 2006, only 13 cases of acute non‐lymphoblastic leukemia were registered (mean person‐years at risk 4.3) …”
Section: Introductionmentioning
confidence: 99%
“…10 Reports on a general unselected CLL population are based on cancer registries. 11,12 Among 15 915 patients with CLL surviving at least 1 year after diagnosis of CLL registered in 11 SEER registries in USA between 1992 and 2006, only 13 cases of acute non-lymphoblastic leukemia were registered (mean person-years at risk 4.3). 5 Treatment of CLL is about to change dramatically; from therapy based on cytotoxic drugs, to therapy based on drugs targeting signaling pathways, and importantly, free for cytotoxic drugs.…”
mentioning
confidence: 99%
“… 3 Moreover, the risk of SPM in patients with chronic lymphocytic leukemia (CLL) as well as the epidemiologic correlation of melanoma with CLL has been studied by several teams. 1 9 …”
Section: Introductionmentioning
confidence: 99%